Caracterización morfométrica de la microcuenca del Caño Caribito en el municipio de Puerto Lleras - Meta a partir de un modelo digital de elevación (2023)
Geographic information systems, as instruments for interactive data and information consultation, are mainly in the public domain, however, their use has been limited to a selective professional or technical population, or to the development by public entities in the exercise of their mission activities, being necessary and also useful tools for the knowledge of the general population.